Multiple-choice reaction and visual perception in female and male elite athletes - Dogan, B. (The Journal of Sports Medicine and Physical Fitness, 2009)
Aim. The aim of this study was to determine multiple-choice reaction and visual perception in female and male elite athletes. Methods. A total of 49 athletes (26 males, 23 females) with a mean age of 21.84 ± 1.94 in the range of 18-26 years participated in this study. Participants were college athletes participating in basketball, soccer, handball, volleyball, gymnastics, fencing and swimming. Two tests were applied to investigate the multiple-choice reaction and visual perception of athletes: Vienna Determination Test and Visual Pursuit Test. Results. The results indicated that male athletes had lower total amount of incorrect responses to a stimulus, compared with female athletes and that individual sports had a higher total amount of omitted responses given to a stimulus, compared with team sports. For "on time" response, there were significant differences for individual and team sports in interval 3. Depending on the sport branch, significant differences were found between male and female athletes in the amount of omitted responses given to a stimulus response in interval 3. Conclusion. The results of this study support the importance of reaction time related to aspects of the sports branch.